2018
DOI: 10.1515/hsz-2017-0215
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA KCNQ1OT1 ameliorates particle-induced osteolysis through inducing macrophage polarization by inhibiting miR-21a-5p

Abstract: This study aimed to investigate the mechanism of lncRNA-KCNQ1OT1 on macrophage polarization to ameliorate particle-induced osteolysis. We used polymethylmethacrylate (PMMA) to induce primary bone marrow-derived macrophages (BMMs) obtained from mice and the RAW264.7 cell line, and found that the tumor necrosis factor-alpha (TNF-α) concentration and inducible nitric oxide synthase (iNOS) expression was increased, while interleukin (IL)-10 concentration and Arg1 expression were decreased in PMMA-induced cells. KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Over the years, accumulating evidence exists with regard to the importance of lncRNA KCNQ1OT1in the development of musculoskeletal system. A recent study indicated that lncRNA KCNQ1OT1 ameliorated particle-induced osteolysis through inducing macrophage polarization by suppressing miR-21a-5p [21]. The present study showed that lncRNA KCNQ1OT1 was up-regulated in the injured tendon specimens of tendon injury mice model and during osteogenic and adipogenic differentiation of TSCs, which suggested that KCNQ1OT1 might involve in the osteogenic and adipogenic changes.…”
Section: Discussionsupporting
confidence: 58%
“…Over the years, accumulating evidence exists with regard to the importance of lncRNA KCNQ1OT1in the development of musculoskeletal system. A recent study indicated that lncRNA KCNQ1OT1 ameliorated particle-induced osteolysis through inducing macrophage polarization by suppressing miR-21a-5p [21]. The present study showed that lncRNA KCNQ1OT1 was up-regulated in the injured tendon specimens of tendon injury mice model and during osteogenic and adipogenic differentiation of TSCs, which suggested that KCNQ1OT1 might involve in the osteogenic and adipogenic changes.…”
Section: Discussionsupporting
confidence: 58%
“…82 KCNQ1OT1 could function as a miR-21a-5p decoy to up-regulate IL-10, induced polarization of macrophages into M2 type. 83,84 LncRNA TCONS_00019715 was expressed at a higher level when M2 macrophage was converted to M1, but decreased when M1 type was converted to M2 85…”
Section: Lncrnas Expression Profile In M1-like Macrophagementioning
confidence: 99%
“…HOTTIP expression was associated with TLR tolerance, and has been speculated to skew macrophage polarization to a “M2‐like” phenotype . KCNQ1OT1 could function as a miR‐21a‐5p decoy to up‐regulate IL‐10, induced polarization of macrophages into M2 type . LncRNA TCONS_00019715 was expressed at a higher level when M2 macrophage was converted to M1, but decreased when M1 type was converted to M2…”
Section: Lncrnas Involve In Human Monocyte/macrophage Differentiationmentioning
confidence: 99%
See 2 more Smart Citations